Softening agent

A flexible base containing internal olefin sulfonate and a specific compound addresses the hardening of textiles by enhancing fiber softness and flexibility, ensuring uniform treatment and improved texture.

JP7609633B2Active Publication Date: 2025-01-07KAO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020217305
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-01-07
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

Textile products become hard and develop an undesirable texture with repeated use and washing, and existing softener compositions, particularly those with cationic surfactants, do not effectively address this issue.

Method used

A flexible base comprising internal olefin sulfonate (IOS) and a compound represented by formula (B-1) is used to treat fibers, providing enhanced flexibility and softness.

Benefits of technology

The flexible base effectively softens fibers, offering improved texture and flexibility, especially when used in conjunction with relatively hard water, and ensures uniform treatment through optimized aqueous dispersion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609633000001
    Figure 0007609633000001
  • Figure 0007609633000002
    Figure 0007609633000002
  • Figure 0007609633000003
    Figure 0007609633000003
Patent Text Reader

Abstract

To provide a novel softening base agent having a high effect of softening fibers.SOLUTION: A softening base agent contains (A) an internal olefin sulfonate and (B) a compound represented by the following formula (B-1). Desirably, (A) has a C15-30 hydrocarbon group; and R1 and R2 in formula (B-1) each denote a C7-20 alkyl group or alkenyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a softening base, a fiber treatment composition, and a method for treating fibers. [Background technology]

[0002] When textile products such as clothing are repeatedly worn and washed, they gradually become stiff and develop an undesirable texture. To improve this, fabric softeners are added to the rinsing process of the laundry to soften the fabric. Currently, many of the fabric softener compositions available on the market contain a cationic surfactant as an active ingredient, but fabric softener compositions containing an anionic surfactant have been investigated (Patent Documents 1 to 4).

[0003] Patent Document 1 discloses a fabric softener containing a sulfosuccinate salt-type anionic surfactant, a polyethylene polyamine higher fatty acid amide-type cationic surfactant, a nonionic surfactant, and polysiloxanes. Patent Document 2 discloses an antibacterial fabric softener composition containing an anionic fabric softener composition containing as essential components a cationic bactericide such as benzalkonium chloride, a metal chelating agent, and a salt of a dialkylsulfosuccinic acid having an alkyl group with 16 or more carbon atoms. Patent Document 3 discloses that in a fabric detergent composition containing an internal olefin sulfonate having from 17 to 24 carbon atoms, a nonionic surfactant, and a metal ion chelating agent, the internal olefin sulfonate having a specific carbon chain length has the effect of softening fabrics. Patent Document 4 discloses a fiber modifier that is made of an internal olefin sulfonate having 17 to 24 carbon atoms and that gives a fiber product a soft feel. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-311575 [Patent Document 2] Japanese Patent Application Publication No. 8-158258 [Patent Document 3] JP 2017-214567 A [Patent Document 4] JP 2018-66102 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention provides a novel softening base that is excellent in the effect of softening fabrics. [Means for solving the problem]

[0006] The present invention relates to a softening agent containing (A) an internal olefin sulfonate salt (hereinafter referred to as component (A)) and (B) a compound represented by the following formula (B-1) (hereinafter referred to as component (B)).

[0007] [ka] (In the formula, R 1 and R 2 Each represents a hydrocarbon group, and M is a cation (excluding hydrogen ions).

[0008] The present invention also relates to a fiber treatment composition containing the softening base.

[0009] The present invention also relates to a method for treating fibers, in which the fibers are treated with component (A) and component (B). Effect of the Invention

[0010] According to the present invention, there is provided a softening base having an excellent effect of softening fabrics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Softening agent] The softening base of the present invention contains (A) an internal olefin sulfonate salt [hereinafter referred to as component (A)] and (B) a compound represented by the above formula (B-1) [hereinafter referred to as component (B)]. The softening base of the present invention means an agent (active ingredient) that imparts softness to fibers. The softening base of the present invention may be composed of component (A) and component (B). The softening base of the present invention may be a softening base composition containing component (A) and component (B). The softening base of the present invention can exert a more excellent softening effect by being mixed with water having a relatively high hardness.

[0012] The component (A) may include one or more types of internal olefin sulfonate.

[0013] From the viewpoint of imparting flexibility, the internal olefin sulfonate is preferably an internal olefin sulfonate having a hydrocarbon group having a carbon number of 15 to 30. Hereinafter, the internal olefin sulfonate may be abbreviated as IOS. IOS can be obtained, for example, by sulfonating, neutralizing, and hydrolyzing an internal olefin in which the double bond is located inside the olefin chain (at the 2nd or higher position). When an internal olefin is sulfonated, β-sultone is quantitatively produced, and a part of the β-sultone is converted to γ-sultone and olefin sulfonic acid, which are further converted to hydroxyalkanesulfonate (H-form) and olefinsulfonate (O-form) in the neutralization and hydrolysis process (e.g., J. Am. Oil Chem. Soc. 69, 39(1992)). IOS is a mixture of these, and is mainly a sulfonate in which the sulfonic acid group is located inside (at the 2nd or higher position) of the hydrocarbon chain (hydroxyalkane chain in H-form, or olefin chain in O-form). The substitution position distribution of the sulfonic acid group in the hydrocarbon chain of IOS can be quantified by methods such as gas chromatography and nuclear magnetic resonance spectroscopy.

[0014] In terms of imparting flexibility, the proportion of IOS in which a sulfonic acid group is present at the second position of the hydrocarbon chain in the IOS, which is component (A), is preferably 5% or more, more preferably 10% or more, even more preferably 20% or more, on a molar or mass basis, and is preferably 45% or less, more preferably 30% or less.

[0015] In the IOS, which is the component (A), the proportion of IOS in which a sulfonic acid group is present at position 1 of the hydrocarbon chain is, from the viewpoint of imparting flexibility, preferably 0.2% or more, more preferably 1% or more, even more preferably 2% or more, and is preferably 20% or less, more preferably 10% or less, even more preferably 5% or less, and still more preferably 3% or less, on a molar or mass basis.

[0016] The carbon number of the hydrocarbon group of IOS, which is component (A), is preferably 15 or more, more preferably 16 or more, even more preferably 17 or more, and still more preferably 18 or more from the viewpoint of imparting flexibility, and is preferably 30 or less, more preferably 25 or less, and even more preferably 20 or less, from the viewpoint of improving cleaning performance. The hydrocarbon group in IOS, which is the component (A), is preferably a linear or branched alkyl group, more preferably a branched alkyl group, from the viewpoint of imparting flexibility.

[0017] In the IOS, which is component (A), the proportion of IOS having a hydrocarbon group having 15 to 30 carbon atoms is, from the viewpoint of imparting flexibility, preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, still more preferably 90 mass% or more, still more preferably 95 mass% or more, still more preferably 97 mass% or more, and is preferably 100 mass% or less, and may be 100 mass%.

[0018] The IOS having a hydrocarbon group having 15 to 30 carbon atoms, which is component (A), has a molar ratio of H-form to O-form (H-form / O-form) of preferably 50 / 50 or more, more preferably 70 / 30 or more, from the viewpoint of imparting flexibility, and is preferably 95 / 5 or less, more preferably 90 / 10 or less.

[0019] Examples of the internal olefin sulfonate include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium and barium; and organic ammonium salts such as triethanolammonium, diethanolammonium, monoethanolammonium, trimethylammonium, and monomethylammonium. From the viewpoint of flexibility, alkali metal salts and alkanol ammonium salts are preferred, sodium salts, potassium salts, triethanol ammonium salts, diethanol ammonium salts and monoethanol ammonium salts are more preferred, and sodium salts are even more preferred.

[0020] The component (B) is a compound represented by the following formula (B-1).

[0021] [ka] (In the formula, R 1 and R 2 Each represents a hydrocarbon group, and M is a cation (excluding hydrogen ions).

[0022] Component (B) is a sulfosuccinate having two hydrocarbon groups with a specific structure, which has excellent dispersion stability in aqueous systems and can impart excellent flexibility to fibers. The reason for this effect is unclear, but it is thought to be as follows. In general, anionic surfactants such as sulfonate type surfactants having long alkyl chains have a high Krafft point and are easily aggregated and separated in water. In an aggregated dispersion, it is difficult to uniformly treat fibers even if the fibers are treated in a bath, and performance is not easily exhibited. On the other hand, in the present invention, the compound represented by formula (B-1) has a specific structure and a specific hydrocarbon group (e.g., the number of carbon atoms in the alkyl group, the structure of the alkyl group), and hydrophilicity, aggregation, and curvature are optimized, so that a stable aqueous dispersion can be obtained. It is presumed that by treating fibers in such a stable dispersion state, uniformity and efficient treatment can be performed, resulting in excellent fiber modification effects. Note that the present invention is not limited to this mechanism.

[0023] In formula (B-1), R 1 and R 2 may be the same or different, and each is preferably a hydrocarbon group having a carbon number of 7 to 20. Examples of the hydrocarbon group include an alkyl group and an alkenyl group. In formula (B-1), R 1 and R 2 From the viewpoint of flexibility, the number of carbon atoms in the hydrocarbon group is preferably 7 or more, more preferably 12 or more, and from the viewpoint of dispersibility, the number of carbon atoms is preferably 20 or less, more preferably 18 or less. R 1 and R 2 Combination of (R 1 / R 2 or R 2 / R 1 From the viewpoints of flexibility and dispersibility, the copolymer is preferably an oleyl group / 2-butyloctyl group or an isotridecyl group / isotridecyl group, and more preferably an oleyl group / 2-butyloctyl group.

[0024] In formula (B-1), R 1 and R 2 From the viewpoint of flexibility, the total number of carbon atoms is preferably 14 or more, more preferably 20 or more, even more preferably 22 or more, and even more preferably 25 or more, and from the viewpoint of dispersibility, it is preferably 32 or less, more preferably 30 or less. 1 and R 2In the case where the softening agent contains two or more compounds with different total carbon numbers, R 1 and R 2 The total number of carbon atoms in each compound is R 1 and R 2 represents the molar average of the total carbon number.

[0025] In formula (B-1), R 1 and R 2 The hydrocarbon group may be either a straight chain or a branched chain, but from the viewpoints of flexibility and dispersibility, it is preferable that the hydrocarbon group contains a branched chain. In formula (B-1), R 1 and R 2 The hydrocarbon group may be either saturated or unsaturated, but from the viewpoints of flexibility and dispersibility, it is preferable that the hydrocarbon group contains an unsaturated group. Therefore, in the formula (B-1), R 1 and R 2 At least one of them is preferably a hydrocarbon group having a branched chain structure or an unsaturated bond. In formula (B-1), R 1 and R 2 From the viewpoint of flexibility and dispersibility, the hydrocarbon group more preferably contains a saturated branched chain or an unsaturated straight chain, and even more preferably contains a saturated branched chain and an unsaturated straight chain.

[0026] In formula (B-1), R 1 The hydrocarbon group and R 2 The hydrocarbon groups in R may be the same or different. 1 The hydrocarbon group and R 2 In the case where the hydrocarbon groups of R are different, this is preferable from the viewpoint of flexibility. 1 The hydrocarbon group and R 2 In the case where the hydrocarbon groups in R are the same, this is preferred from the viewpoints of dispersion stability, ease of production, and flexibility at low concentrations or low hardness. 1 The number of carbon atoms and R 2 The carbon numbers of R may be the same or different. 1 The number of carbon atoms and R 2 In terms of flexibility, it is preferable that the carbon numbers of R are different. 1 The number of carbon atoms and R 2The case where the carbon numbers of are the same is preferable from the viewpoints of dispersion stability, ease of production, and flexibility at low concentration or low hardness.

[0027] The component (B) is a compound represented by the formula (B-1), 1 and R 2 are hydrocarbon groups of the same structure, and R 1 and R 2 may be one or more compounds selected from compounds in which From the viewpoint of flexibility, the (B) component is R 1 and R 2 are preferably hydrocarbon groups having different structures. For example, the softening base of the present invention is 1 and R 2 The compound represented by the formula (B-1), 1 and R 2 may contain a compound represented by the formula (B-1) in which

[0028] In formula (B-1), M is a cation (excluding hydrogen ion). Examples of M include alkali metal ions such as lithium ion, sodium ion, and potassium ion, alkaline earth metal ions such as calcium ion and barium ion, and organic ammonium ions such as triethanolammonium ion, diethanolammonium ion, monoethanolammonium ion, trimethylammonium ion, and monomethylammonium ion. From the viewpoint of dispersion stability and flexibility, M is preferably an alkali metal ion or an alkanol ammonium ion, more preferably a sodium ion, a potassium ion, a triethanol ammonium ion, a diethanol ammonium ion or a monoethanol ammonium ion, and further preferably a sodium ion.

[0029] The component (B) can be synthesized by a known method. For example, it can be obtained by reacting a maleic acid diester obtained by reacting maleic anhydride with an alcohol with a hydrogen sulfite. In this case, by using alcohols with different carbon numbers or structures, the R 1 and R 2 In the case of the compound (B), the hydrocarbon group has a different structure. The component (B) can be synthesized, for example, by the method described in Examples 2 and 3 of US Patent Application Publication No. 2007 / 0214999.

[0030] In the softening agent of the present invention, the mass ratio (A) / (B) of the contents of the components (A) and (B) in the composition is preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, still more preferably 1.5 or less, and even more preferably 1.2 or less from the viewpoint of flexibility, and is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and even more preferably 0.8 or more from the viewpoints of mixability, handling, and flexibility. The masses of the components (A) and (B) are expressed in terms of sodium salts (the same applies hereinafter).

[0031] The soft base of the present invention can be applied to various fibers, such as natural fibers, synthetic fibers, and semi-synthetic fibers. Furthermore, the soft base of the present invention can be applied to textile products containing these fibers.

[0032] The fibers may be either hydrophobic or hydrophilic. Examples of hydrophobic fibers include protein fibers (milk protein casein fibers, promix, etc.), polyamide fibers (nylon, etc.), polyester fibers (polyester, etc.), polyacrylonitrile fibers (acrylic, etc.), polyvinyl alcohol fibers (vinylon, etc.), polyvinyl chloride fibers (polyvinyl chloride, etc.), polyvinylidene chloride fibers (vinylidene, etc.), polyolefin fibers (polyethylene, polypropylene, etc.), polyurethane fibers (polyurethane, etc.), polyvinyl chloride / polyvinyl alcohol copolymer fibers (polycral, etc.), polyalkylene paraoxybenzoate fibers (benzoate, etc.), and polyfluoroethylene fibers (polytetrafluoroethylene, etc.). Examples of hydrophilic fibers include seed hair fibers (cotton, cotton, kapok, etc.), bast fibers (hemp, flax, ramie, hemp, jute, etc.), leaf vein fibers (Manila hemp, sisal, etc.), palm fibers, rush, straw, animal hair fibers (wool, mohair, cashmere, camel hair, alpaca, vicuna, angora, etc.), silk fibers (domestic silk, wild silk), feathers, and cellulosic fibers (rayon, polynosic, cupra, acetate, etc.). The fiber is preferably a fiber containing cotton fiber. From the viewpoint of further improving the softness of the fiber, the content of cotton fiber in the fiber is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, still more preferably 20% by mass or more, and even more preferably 100% by mass. In the present invention, the textile product may be a fabric such as a woven fabric, knitted fabric, or nonwoven fabric using the hydrophobic or hydrophilic fiber, and products obtained using the same such as an undershirt, T-shirt, dress shirt, blouse, slacks, hat, handkerchief, towel, knitwear, socks, underwear, or tights. From the viewpoint of making it easier to feel the improvement in texture of the fiber after treatment with the fiber treatment composition of the present invention, the textile product is preferably a textile product containing cotton fiber. The preferred embodiment of the content of cotton fiber in the textile product is the same as the content of cotton fiber in the above-mentioned fiber.

[0033] The softening agent of the present invention can impart softness to fibers. When the softening agent of the present invention is mixed with water having a relatively high hardness, it can impart excellent softness to fibers. In addition, the softening agent of the present invention has excellent dispersibility when mixed with water.

[0034] [Fiber treatment composition] The present invention provides a fiber treatment composition containing component (A) and component (B) as a softening base. The fiber treatment composition of the present invention may be a fiber treatment composition containing the softening base of the present invention. The fiber treatment composition of the present invention may be a fiber treatment composition containing component (A) and component (B) as active ingredients of a softener. The matters described for the softening base of the present invention can be appropriately applied to the fiber treatment composition of the present invention. Specific examples and preferred aspects of component (A) and component (B) are the same as those of the softening base of the present invention.

[0035] In the fiber treatment composition of the present invention, the content of component (A) is preferably 0.1 mass% or more, more preferably 1 mass% or more, and even more preferably 4 mass% or more from the viewpoints of product transportation, mixability, and softness retention, and from the viewpoint of handleability, it is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 15 mass% or less.

[0036] In the fiber treatment composition of the present invention, the content of component (B) is preferably 0.1 mass % or more, more preferably 1 mass % or more, and even more preferably 4 mass % or more, from the viewpoints of product transportation, mixability, and softness retention, and from the viewpoint of handleability, it is preferably 30 mass % or less, more preferably 25 mass % or less, and even more preferably 20 mass % or less.

[0037] In the fiber treatment composition of the present invention, the mass ratio (A) / (B) of the contents of the component (A) and the component (B) in the composition is, from the viewpoint of flexibility, preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, still more preferably 1.5 or less, and even more preferably 1.2 or less, and from the viewpoints of mixability, handleability, and flexibility, it is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and even more preferably 0.8 or more.

[0038] The fiber treatment composition of the present invention preferably contains water. It is preferably a liquid composition containing water. Water is usually the remainder of the composition and is used in an amount such that the total of the composition is 100% by mass.

[0039] The fiber treatment composition of the present invention may contain an organic solvent in addition to components (A) and (B). Examples of the organic solvent include butyl diglycol (BDG), propylene glycol (PG), ethanol, and isopropanol.

[0040] The fiber treatment composition of the present invention may be a fabric softener composition. For example, the present invention can provide a fabric softener composition containing the components (A) and (B) as active ingredients of a softening base.

[0041] [Textile processing method] The present invention provides a method for treating fibers with component (A) and component (B). The method for treating fibers of the present invention may be a method for treating fibers with the softening base of the present invention or the fiber treatment composition of the present invention. The matters described for the softening base and fiber treatment composition of the present invention can be appropriately applied to the method for treating fibers of the present invention. Specific examples and preferred aspects of component (A) and component (B) are the same as those of the softening base of the present invention.

[0042] In the present invention, from the viewpoint of flexibility, the ratio of the total mass of components (A) and (B) to the mass of the fiber (textile product) is preferably 0.01% owf or more, more preferably 0.05% owf or more, even more preferably 0.1% owf or more, still more preferably 0.2% owf or more, still more preferably 0.3% owf or more, and from the viewpoint of texture, it is preferably 5% owf or less, more preferably 4% owf or less, still more preferably 3% owf or less, still more preferably 2% owf or less. Note that "% owf" is an abbreviation for "% on the weight of fabric" and means the percentage of the total mass of components (A) and (B) to the mass of the fiber.

[0043] In the present invention, the treatment liquid obtained by mixing the (A) component, the (B) component, and water can be contacted with fibers. In addition, in the present invention, the treatment liquid obtained by mixing the softening base of the present invention or the fiber treatment composition of the present invention and water can be contacted with fibers. For example, the treatment liquid can be used so that the total mass of the (A) component and the (B) component is within the above range relative to the mass of the fibers.

[0044] The content of component (A) in the treatment liquid used in the fiber treatment method of the present invention is, from the viewpoints of mixability and softness retention, preferably 1 ppm or more, more preferably 5 ppm or more, even more preferably 10 ppm or more, even more preferably 20 ppm or more, and even more preferably 30 ppm or more, and from the viewpoint of handleability, preferably 5000 ppm or less, more preferably 3000 ppm or less, even more preferably 2000 ppm or less, even more preferably 1000 ppm or less, even more preferably 800 ppm or less, even more preferably 300 ppm or less, even more preferably 240 ppm or less, even more preferably 200 ppm or less, even more preferably 120 ppm or less, and even more preferably 100 ppm or less.

[0045] The content of component (B) in the treatment liquid used in the fiber treatment method of the present invention is, from the viewpoints of mixability and softness retention, preferably 1 ppm or more, more preferably 5 ppm or more, even more preferably 10 ppm or more, more preferably 20 ppm or more, even more preferably 30 ppm or more, even more preferably 40 ppm or more, even more preferably 50 ppm or more, and even more preferably 60 ppm or more, and from the viewpoint of handleability, preferably 5000 ppm or less, more preferably 3000 ppm or less, even more preferably 2000 ppm or less, even more preferably 1000 ppm or less, even more preferably 800 ppm or less, even more preferably 300 ppm or less, even more preferably 240 ppm or less, even more preferably 200 ppm or less, even more preferably 120 ppm or less, and even more preferably 100 ppm or less.

[0046] The mass ratio (A) / (B) of the contents of the component (A) and the component (B) in the treatment liquid used in the fiber treatment method of the present invention is, from the viewpoint of softness, preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, still more preferably 2 or less, still more preferably 1.5 or less, and still more preferably 1.2 or less, and from the viewpoints of mixability, handleability, and softness, it is preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and still more preferably 0.8 or more.

[0047] In the present invention, it is preferable to use the components (A) and (B) mixed with water having a hardness of 0° dH or more and 30° dH or less. That is, it is preferable to treat fibers with a treatment liquid obtained by mixing the components (A) and (B) with water having a hardness of 0° dH or more and 30° dH or less. From the viewpoint of softness, the hardness of the water is preferably 3° dH or more, more preferably 5° dH or more, more preferably 7° dH or more, more preferably 8° dH or more, more preferably 10° dH or more, and more preferably 15° dH or more, and from the viewpoint of texture, it is preferably 25° dH or less, more preferably 20° dH or less. The fibers can also be treated with a treatment liquid obtained by mixing the water with the softening base or fiber treatment composition of the present invention.

[0048] <How to measure water hardness> 〔reagent〕 0.01 mol / l EDTA·2Na solution: 0.01 mol / l aqueous solution of disodium ethylenediaminetetraacetate (titration solution, 0.01 M EDTA-Na2, manufactured by Sigma-Aldrich) ·Universal BT indicator (product name: Universal BT, manufactured by Dojindo Laboratories Co., Ltd.) Ammonia buffer solution for hardness measurement (67.5 g of ammonium chloride dissolved in 570 ml of 28 w / v% ammonia water, and made up to 1000 ml with deionized water) [Measurement of hardness] (1) Using a volumetric pipette, place 20 ml of sample water into a conical beaker. (2) Add 2 ml of ammonia buffer solution for hardness measurement. (3) Add 0.5 ml of Universal BT indicator and confirm that the solution is reddish purple after addition. (4) While shaking the conical beaker well, add 0.01 mol / l EDTA·2Na solution dropwise from the burette until the sample water turns blue, which is the endpoint of the titration. (5) Total hardness is calculated using the following formula. Hardness (°dH)=T×0.01×F×56.0774×100 / A T:0.01mol / l Titration amount of EDTA・2Na solution (mL) A: Sample volume (20 mL, volume of sample water) F: Factor of 0.01mol / l EDTA·2Na solution

[0049] The method for treating fibers of the present invention can be directed to the fibers described in the softening base of the present invention. For example, the fibers can be fabric fibers.

[0050] The method for treating fibers of the present invention can be incorporated into a washing process for fibers, such as cloth fibers. Here, the washing process may be a process for washing, rinsing, and dehydrating the fibers. In the present invention, the softening agent of the present invention can be applied to the fibers in any of these washing processes so that the components (A) and (B) are in predetermined amounts. EXAMPLES

[0051] <Production example of component (A)> Component (A), sodium internal olefin sulfonate (IOS) having 18 carbon atoms, was produced by the following method. First, 7000 g of 1-octadecanol (Kao Corporation's "Kalcol 8098") and 700 g of γ-alumina (Strem Chemicals Inc.'s) as a catalyst were charged into a flask equipped with a stirrer, and the reaction was carried out at 280°C under stirring while circulating nitrogen (7000 mL / min.) through the system, adjusting the reaction time appropriately, to obtain a crude internal olefin. The crude internal olefin was distilled at 148-158°C and 0.5 mmHg to obtain an internal olefin with a carbon number of 18 and an olefin purity of 100%. The internal olefin was subjected to a sulfonation reaction using a thin-film sulfonation reactor having an external jacket, with cooling water at 20°C passed through the reactor's external jacket, and sulfonation reaction was carried out using sulfur trioxide gas. The molar ratio of SO3 / internal olefin during the sulfonation reaction was set to 1.09. The obtained sulfonated product was added to an alkaline aqueous solution prepared with 1.5 moles of sodium hydroxide relative to the theoretical acid value, and neutralized with stirring at 30° C. for 1 hour. The neutralized product was heated in an autoclave at 170° C. for 1 hour to carry out hydrolysis, thereby producing sodium internal olefin sulfonate having 18 carbon atoms.

[0052] <Production Examples 1 to 6 of Component (B)> The sodium dialkyl sulfosuccinate of each production example shown in Table 1 was prepared as follows. The raw materials and catalyst used in the preparation of the maleic acid diester shown in Table 1 were charged in the amounts shown in Table 1 into a reaction vessel shown in Table 1 equipped with a stirring device, a heating system, a distillation column, and nitrogen / vacuum connection, and after nitrogen replacement, the mixture was reacted under nitrogen bubbling at 100 to 130°C while dehydrating until the acid value was reduced to the equivalent amount of p-toluenesulfonic acid. The catalyst was then adsorbed using Kyoward 500SH (manufactured by Kyowa Chemical Industry Co., Ltd.) at 1% by mass relative to the total amount of the reaction vessel contents. After removing the adsorbent, the excess alcohol was removed by topping to obtain a maleic acid diester.

[0053] Next, the maleic acid diester obtained above, sodium disulfite, and ion-exchanged water were charged in the amounts shown in Table 1 into a 1L glass reaction vessel, and in order to improve the compatibility of the raw materials used in the preparation of sodium dialkyl sulfosuccinate shown in Table 1, a polar alcoholic solvent such as ethanol was used, and the mixture was reacted at 115°C by a known method until the double bond derived from the maleic acid diester disappeared by NMR. The mixture was cooled to 50-65°C, and the remaining sodium hydrogen sulfite was oxidized with 30% hydrogen peroxide, and then the pH was adjusted to 5 with 10% NaOH. The solvent and sodium sulfate were removed by distillation under reduced pressure, reprecipitation, separation, etc., to obtain sodium dialkyl sulfosuccinate shown in Table 1.

[0054] [Table 1]

[0055] The ingredients in Table 1 are as follows: Maleic anhydride: Fujifilm Wako Pure Chemical Industries, Ltd., Wako special grade 2-Propylheptanol: Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent 2-Butyl-1-n-octanol: Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent Dodecanol: "Kalcol 2098" manufactured by Kao Corporation Oleyl alcohol: Alfa Aesar Isodecanol: "Decanol" manufactured by KH Neochem Isotridecanol: "Tridecanol" manufactured by KH Neochem p-Toluenesulfonic acid monohydrate: Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent Sodium disulfite: Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent

[0056] Table 1 shows the structures of B1 to B6 in the formula (B-1) of the component (B). The symbols in parentheses indicate the alkyl groups (R 1 , R 2 (abbreviation for B1: Sodium di(2-propylheptyl)-sulfosuccinate prepared in Production Example 1, (PH / PH) B2: Sodium di(2-butyloctyl)-sulfosuccinate (BO / BO) prepared in Production Example 2 B3: sodium dodecyl / 2-butyloctyl sulfosuccinate (C12 / BO) prepared in Production Example 3 B4: Sodium oleyl / 2-butyloctyl sulfosuccinate (C18F1 / BO) prepared in Production Example 4 B5: Sodium di(isodecyl)-sulfosuccinate (di-isoC10) prepared in Production Example 5 B6: Sodium di(isotridecyl)-sulfosuccinate (di-isoC13) prepared in Production Example 6

[0057] <Preparation of Examples 1 to 13 and Comparative Examples 1 and 2> The components (A) and (B) produced by the above methods were prepared according to the compositions shown in Table 2, to give the fiber treatment compositions of Examples 1 to 13 and Comparative Examples 1 and 2. The fiber treatment compositions of each of the Examples and Comparative Examples were subjected to the following softness evaluation. The results are shown in Table 2.

[0058] How to evaluate flexibility 1) Pretreatment of evaluation towels The towels used for evaluation were previously subjected to the following treatment to remove starch and impurities. Using a fully automatic washing machine (manufactured by Panasonic, model number: NA-F60PB3), 24 commercially available cotton towels (TW220, white, manufactured by Takei Towel Co., Ltd.) were washed three times with 52.22 g of a 10% diluted solution of a nonionic surfactant (manufactured by Kao Corporation, Emulgen 108) as detergent and tap water from Wakayama City as water (50 L of water, 10 minutes of washing → 2 rinses and 9 minutes of spinning). The above series of washing steps was then repeated twice using water only. The towels were then left to stand at room temperature (25°C) for 24 hours and naturally dried.

[0059] 2) How to dispose of towels A predetermined amount of ion-exchanged water (bath ratio 25L / kg-towel) was put into a mini-mini washing machine (National, model number: NA-35), and a calcium chloride aqueous solution (equivalent to 4000°dH) was added so that the hardness was that of Table 2. The fiber treatment composition of Table 2 was added while stirring, and after stirring for 1 minute, three cotton towels (total of about 210g) pretreated in the above 1) were put in and treated for 5 minutes under stirring. In this treatment, the amount of softener used was adjusted so that the treatment amount (%owf) of Table 2 was obtained based on three cotton towels. Next, the cotton towels were dehydrated for 3 minutes in the dehydration tank of a two-tub washing machine (TOSHIBA, model number: VH-52G(H)), and dried for 24 hours in a constant temperature and humidity room at 23°C and 40%RH.

[0060] 3) Flexibility assessment As a benchmark, cotton towels were prepared that were treated using the methods 1) and 2) described above, with the recipes for each score below. The softness of cotton towels treated with the fabric softeners shown in Table 2 was compared with the softness of a standard cotton towel to evaluate the softness. The evaluation was carried out by five panelists who each assigned a score based on the following criteria, and the average values ​​are shown in the table. In addition, in evaluating the towels, each panelist was allowed to assign a decimal point between each score. The higher the score, the better the softness. Score 1: Softness equivalent to that of a product processed using only 20℃ tap water Score 2: Equivalent to softness achieved by treatment with a formula using the index softener at 0.025% owf in 20°C tap water Score 3: Equivalent to softness achieved by treatment with a formula using the index softener at 0.050% owf in 20°C tap water Score 4: Equivalent to softness achieved by treatment with a formula using the index softener at 0.075% owf in 20°C tap water Score 5: Equivalent to softness achieved by treatment with a formula using the index softener at 0.100% owf in 20°C tap water Here, the indicator softening base used was esteramide hydrochloride (2-[N-[3-alkanoyl(C14-20)aminopropyl]-N-methylamino]ethyl alkano(C14-20)ate hydrochloride).

[0061] [Table 2]

Claims

1. A softening base comprising (A) an internal olefin sulfonate salt (hereinafter referred to as component (A)) and (B) a compound represented by the following formula (B-1) (hereinafter referred to as component (B)): 【Chemistry 1】 (In the formula, R 1 and R 2 each represents a hydrocarbon group, the total number of carbon atoms in R 1 and R 2 is 20 to 32, and M is a cation (excluding hydrogen ion).

2. 2. The softening base according to claim 1, wherein the component (A) is an internal olefin sulfonate having a hydrocarbon group having 15 to 30 carbon atoms.

3. In the formula (B-1), R 1 and R 2 are each an alkyl or alkenyl group having 7 to 20 carbon atoms, R 1 and R 2 The softening agent according to claim 1 or 2, wherein the total number of carbon atoms is 20 or more and 32 or less.

4. In the formula (B-1), R 1 and R 2 The softening agent according to any one of claims 1 to 3, wherein one or more selected from the following is a hydrocarbon group having a branched chain structure or an unsaturated bond.

5. The softening base according to any one of claims 1 to 4, wherein the mass ratio (A) / (B) of the content of the component (A) to the content of the component (B) is 5 or less.

6. A fabric treatment composition comprising the softening agent according to any one of claims 1 to 5.

7. A method for softening fibers, comprising treating the fibers with (A) an internal olefin sulfonate salt (hereinafter referred to as component (A)) and (B) a compound represented by the following formula (B-1) (hereinafter referred to as component (B)): 【Chemistry 2】 (In the formula, R 1 and R 2 each represents a hydrocarbon group, the total number of carbon atoms in R 1 and R 2 is 20 to 32, and M is a cation (excluding hydrogen ion).

8. The method for softening fibers according to claim 7, wherein the components (A) and (B) are used in amounts such that the ratio of the total mass of the components (A) and (B) to the mass of the fibers is 0.01% o.w.f. or more and 5% o.w.f. or less.

9. 9. The method for softening fibers according to claim 7 or 8, wherein the fibers are treated with a treatment liquid obtained by mixing the component (A), the component (B), and water.

10. The method for softening fibers according to any one of claims 7 to 9, comprising treating fibers with a treatment liquid obtained by mixing the softening base according to any one of claims 1 to 5 or the fiber treatment composition according to claim 6 with water.

11. The method for softening textiles according to claim 9 or 10, wherein the water has a hardness of 0° dH or more and 30° dH or less.

12. The method for softening fibers according to any one of claims 7 to 11, wherein the mass ratio (A) / (B) of the content of the component (A) to the content of the component (B) is 5 or less.

Citation Information

Patent Citations

  • Softening finish agent for fiber

    JP1993311575A

  • Antimicrobial softener composition

    JP1996158258A

  • Antimicrobial softening agent composition

    JP1997137378A

  • Detergent composition for fiber

    JP2017214567A

  • Method for cleaning fiber product

    JP2017214678A